Descriptive epidemiology of screen and non-screen sedentary time in adolescents: a cross sectional study - Ridley Kate; Maher Carol A; Olds Tim S; Kittel Daniella M (International Journal of Behavioral Nutrition and Physical Activity, 2010)
Abstract Background Much attention has been paid to adolescents' screen time, however very few studies have examined non-screen sedentary time (NSST). This study aimed to (1) describe the magnitude and composition of screen sedentary time (SST) and NSST in Australian adolescents, (2) describe the socio-demographic correlates of SST and NSST, and (3) determine whether screen time is an adequate surrogate for total sedentary behaviour in this population. Methods 2200 9-16 year old Australians provided detailed use of time data for four days. Non-screen sedentary time (NSST) included time spent participating in activities expected to elicit <3 METs whilst seated or lying down (other than sleeping), excluding screen-based activities (television, playing videogames or using computers). Total sedentary time was the sum of screen time and NSST. Results Adolescents spent a mean (SD) of 345 (105) minutes/day in NSST, which constituted 60% of total sedentary time. School activities contributed 42% of NSST, socialising 19%, self-care (mainly eating) 16%, and passive transport 15%. Screen time and NSST showed opposite patterns in relation to key socio-demographic characteristics, including sex, age, weight status, household income, parental education and day type. Because screen time was negatively correlated with NSST (r = -0.58), and exhibited a moderate correlation (r = 0.53) with total sedentary time, screen time was only a moderately effective surrogate for total sedentary time. Conclusions To capture a complete picture of young people's sedentary time, studies should endeavour to measure both screen time and NSST.